Accuracy of PDFF estimation by magnitude‐based and complex‐based MRI in children with MR spectroscopy as a reference. Issue 6 (21st March 2017) - Haufe, William M.; Wolfson, Tanya; Hooker, Catherine A.; Hooker, Jonathan C.; Covarrubias, Yesenia; Schlein, Alex N.; Hamilton, Gavin; Middleton, Michael S.; Angeles, Jorge E.; Hernando, Diego; Reeder, Scott B.; Schwimmer, Jeffrey B.; et al.
Abstract : Purpose: To assess and compare the accuracy of magnitude‐based magnetic resonance imaging (MRI‐M) and complex‐based MRI (MRI‐C) for estimating hepatic proton density fat fraction (PDFF) in children, using MR spectroscopy (MRS) as the reference standard. A secondary aim was to assess the agreement between MRI‐M and MRI‐C. Materials and Methods: This was a HIPAA‐compliant, retrospective analysis of data collected in children enrolled in prospective, Institutional Review Board (IRB)‐approved studies between 2012 and 2014. Informed consent was obtained from 200 children (ages 8–19 years) who subsequently underwent 3T MR exams that included MRI‐M, MRI‐C, and T 1 ‐independent, T 2 ‐corrected, single‐voxel stimulated echo acquisition mode (STEAM) MRS. Both MRI methods acquired six echoes at low flip angles. T 2 * ‐corrected PDFF parametric maps were generated. PDFF values were recorded from regions of interest (ROIs) drawn on the maps in each of the nine Couinaud segments and three ROIs colocalized to the MRS voxel location. Regression analyses assessing agreement with MRS were performed to evaluate the accuracy of each MRI method, and Bland–Altman and intraclass correlation coefficient (ICC) analyses were performed to assess agreement between the MRI methods. Results: MRI‐M and MRI‐C PDFF were accurate relative to the colocalized MRS reference standard, with regression intercepts of 0.63% and –0.07%, slopes of 0.998 and 0.975, and proportion‐of‐explained‐variance values (R 2 ) of 0.982 and 0.979, respectively. For individual Couinaud segments and for the whole liver averages, Bland–Altman biases between MRI‐M and MRI‐C were small (ranging from 0.04 to 1.11%) and ICCs were high (≥0.978). Conclusion: Both MRI‐M and MRI‐C accurately estimated hepatic PDFF in children, and high intermethod agreement was observed. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1641–1647.